Box fermentation and solar drying improve the nutrient composition and organoleptic quality of chocolate from cocoa beans - Obinze, Sandra; Ojimelukwe, Philippa C.; Eke, Ben A. (Frontiers in Sustainable Food Systems, 2022)
Chocolate is a well-liked and popular food product made from the cocoa bean. The objective of this research was to evaluate the effects of box fermentation and solar drying of cocoa bean on chocolate quality. Fermentation was carried out in a perforated wooden box for 168 h with periodic turning after every 48 h. The succession of microorganisms during fermentation and total microbial count were monitored. Both the fermented and unfermented samples were solar dried. During drying the change in weight of the beans, amount of solar radiation, and ambient wind speed of the atmosphere were measured. The approximate nutrient (crude protein, crude fat, total ash, crude fiber, and carbohydrate) and phytochemical (phenol) contents of the dried cocoa beans were evaluated. Sensory properties of chocolate, produced from the two samples (box fermented and dried as well as unfermented and dried) were compared. The initial temperature of the fermenting cocoa mash was 30°C. It rose to 46°C by the 96th h of fermentation and sharply declined to 38°C by the 120th h. Candida, Pseudomonas and Staphylococcus spp were probable organisms identified with the fermenting mass at the initial stage of the fermentation. Lactic acid bacteria dominated after 72 h. Bacillus spp was also observed until the 168th h. Solar drying of unfermented bean lasted for 4 days, while that of fermented bean lasted for 3 days. Fermentation increased the crude protein, total ash and carbohydrate contents of the cocoa beans. It also improved the appearance, and aroma of chocolate from the cocoa beans.